The natural characteristics of Medina and its impact on the events of the battle of the parties | الخصائص الطبيعية للمدينة المنورة وأثرها في أحداث غزوة الأحزاب - Al Khateeb | الخطيب, Hamid Musa | حامد موسى (Al-Madinah Al-Munawwarah Research and Studies Center | مركز بحوث ودراسات المدينة المنورة, 2023)
Research topic: pp. 7 - 66 | موضع البحث: ص 7 - 66